Westonci.ca is the Q&A platform that connects you with experts who provide accurate and detailed answers. Explore thousands of questions and answers from a knowledgeable community of experts ready to help you find solutions. Get detailed and accurate answers to your questions from a dedicated community of experts on our Q&A platform.

f (t) = 44 – 5 g(t) = 2t - 1 Find (f - g)(t)

Sagot :

To solve the given problems, we have to subtract the functions.

[tex](f-g)(t)=4t-5-(2t-1)[/tex]

Then, we simplify

[tex](f-g)(t)=4t-5-2t+1=2t-4[/tex]

Hence, the resulting function is 2t-4.